Leadership Style and Reward Systems as Drivers of Employee Work Motivation in the Manufacturing Industry - Kevin Dharmawan; Kiki Sudiana (Greenation International Journal of Economics and Accounting, 2026)
Employee work motivation is essential for improving organizational performance. Nonetheless, earlier research has shown varying results concerning how leadership approaches and incentive structures affect workers' motivation, and there is a scarcity of concrete data from the manufacturing field, especially within the galvanized steel sector. Drawing on Self-Determination Theory, this study examines how leadership style and reward influence employee work motivation by emphasizing the role of organizational support and recognition in fulfilling employees’ psychological needs. A quantitative study that involves 107 permanent employees at an Indonesian galvanized steel company, used questionnaires, along with multiple linear regression. The results suggest that both the type of leadership and the rewards have a noteworthy and positive impact on employees' motivation at work; however, the reward component appears to exert a more powerful influence. In this sense the research extends the support for Self-Determination Theory within manufacturing, and it also gives practical direction for boosting employee motivation by applying leadership that is more aligned and reward mechanisms that are well designed.